Study of the structure of e+e-→bb̄g events and first limits on the anomalous chromomagnetic coupling of the b quark - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Akagi, T; Allen, N; Ash, W; Aston, D; Baird, K; Baltay, C; Band, H; et al. (1999)
The structure of e+e-→bb̄g events was studied using Z0 decays recorded in the SLC Large Detector experiment at SLAC. Three-jet final states were selected and the charge-coupled device-based vertex detector was used to identify two of the jets as b or b. Distributions of the gluon energy and polar angle were measured over the full kinematic range for the first time, and compared with perturbative QCD predictions. The energy distribution is potentially sensitive to an anomalous b chromomagnetic moment κ. We measured κ to be consistent with zero and set the first limits on its value: -0.17<κ<0.11 at 95% C.L. ©1999 The American Physical Society.